2022
DOI: 10.1002/er.8043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of energy consumption in apartment buildings with biochar and phase‐change material aggregate‐applied artificial stone finishing materials

Abstract: Artificial stones for architectural finishing satisfy the aesthetic needs of building occupants and can be easily mixed with other materials. In this study, the thermal inertia of specimens prepared using lightweight aggregate vacuum impregnated with n-octadecane was improved, and the thermal conductivity was improved by mixing biochar having micropores with cement. The applicability of the specimens to apartment buildings in various climatic zones was analyzed. The specimens showed noPCM leakage and were stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Further studies about the biomass-derived porous carbons composite PCMs for building energy efficiency have been proposed by Jiang et al, 2022, and by Kim et al, 2022. In these studies, biochar is recognized as an environmentally friendly product able of enhancing the energy efficiency of buildings.…”
Section: Pinecone Coconut and Others For Biocompositesmentioning
confidence: 99%
“…Further studies about the biomass-derived porous carbons composite PCMs for building energy efficiency have been proposed by Jiang et al, 2022, and by Kim et al, 2022. In these studies, biochar is recognized as an environmentally friendly product able of enhancing the energy efficiency of buildings.…”
Section: Pinecone Coconut and Others For Biocompositesmentioning
confidence: 99%
“…The thermal energy can be effectively stored and released using its phase change characteristics, which is expected to achieve the regulation of the thermal environment [8][9][10]. A large number of literatures have reported that PCMs can be integrated into building envelopes [11][12][13]. The reasonable structure design reduced the temperature fluctuation and improved thermal comfort, which was conducive to reducing energy consumption and rationalizing energy use.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar and PCM‐based interior coatings help to energy savings in buildings. [ 23 ] Nourani et al, explored PCMs made from paraffin and aluminum oxide (Al 2 O 3 ) nanoparticles treated with an SSL emulsifier in another work. The findings revealed that the existence of an SSL emulsifier caused the sample to be stable, but the specimen without SSL was unstable and precipitated after 1 day.…”
Section: Introductionmentioning
confidence: 99%